Comportamento mecânico em fadiga de YSZ: efeitos de diferentes tratamentos de superfície e materiais a base de zircônia - Zucuni, Camila Pauleski (2019)
This thesis are composed of four studies: study 1 – evaluation of fatigue failure load, number of cycles for failure and survival rate in disc of second and third-generation zirconia bonded in the analogue to dentin; study 2 – evaluation and comparison of effect of three polishing systems associated or not to finishing with fine and extra-fine diamond bur, on the surfaces characteristics (roughness and topography), phase transformation and fatigue behavior of a ground Y-TZP ceramic; study 3 – evaluation and comparison of effect of two techniques of glaze application (spray and brush) on the fatigue behavior and surface characteristics (roughness and topography) of Y-TZP ceramic, before and after grinding with diamond bur; study 4 – evaluation of effects of surface treatments (grinding, polishing and glaze) executed on the occlusal surface on its characteristics (roughness and topography), fatigue failure load, number of cycles for failure and phase transformation of an FSZ zirconia cemented adhesively into a similar dentin substrate. In study 1, four second-generation zirconia (Lava Plus, 3M ESPE, Vita In-Ceram YZ-HT, VITA Zahnfabrik, Zirlux FC, Ivoclar Vivadent, Katana ML-HT, Kuraray) and two third-generation zirconia (Katana UTML and Katana STML, Kuraray) were used. Ceramic discs were adhesively cemented onto epoxy resin discs. Fatigue test, fractographic and phase analyzes were performed. In study 2, Y-TZP (Zenostar T) discs were made with: Ø = 15 mm, 1.2 ± 0.2 mm thickness and divided into 8 groups: Ctrl- without treatment; Gr=grinding; Gr + Eve- grinding + polishing with Eve Diacera (two-step system); Gr + Fin + Eve- grinding + finishing + polishing with Eve Diacera; Gr + Kg- grinding + polishing with Kg Viking (two step system); Gr + Fin + Kggrinding + finishing + polishing with K Viking; Gr + Op- polishing with Optrafine (three-step system); Gr + Fin + Op- grinding + finishing + polishing with Optrafine. In the sequence, topography, roughness, phase transformation analysis, fatigue test and fractography were performed; in study 3, the ceramic specimens were divided into 6 groups: Ctrl- without treatment; Gr- grinding with diamond bur; Br - application of glaze powder / liquid; Sp - application of glaze spray; Gr + Br - grinding + glaze powder / liquid; Gr + Sp - grinding + glaze spray. Surface roughness, fatigue test and fracture analysis were performed. In study 4- discs of IPS e.max Zircad MT Multi were produced and divided into 5 groups: Ctrl- without treatment; Gr- grinding with diamond bur; Gr + Pol- grinding + polishing with two step system; Gr + Gl- grinding + application of glaze; Gr + Pol + Gl- grinding + polishing + glaze application. Afterwards, the discs were cemented with resin cement into epoxy resin discs. Surface roughness analysis, fatigue test, fractography and xrd were performed. Regarding the study 1, it was observed that secondgeneration zirconia presents higher load for fatigue failure and number of cycles until failure than third-generation zirconia. In study 2, it was verified that the polishing after grinding reduced the surface roughness and increased the fatigue strength when compared to the control group. However, finishing previously to polishing does not affect surface roughness and fatigue strength. Regarding the study 3, it was observed that the application of glaze, regardless of the application method (brush or spray), does not promote deleterious effects on the fatigue strength of ceramics. In study 4, it was verified that none of the surface treatments performed influenced negatively the fatigue failure load of the ceramic. However, polishing and glaze should be performed after ceramic grinding, as they reduce surface roughness.